The Effect of 20-Minute Mindful Breathing on the Rapid Reduction of Dyspnea at Rest in Patients With Lung Diseases: A Randomized Controlled Trial - Tan, Seng Beng; Liam, Chong Kin; Pang, Yong Kek; Ng, Diana Leh Ching; Wong, Tat Seng; Khoo, Kelvin Wei Shen; Ooi, Chieh Yin; Chai, Chee Shee (Elsevier, 2019)
Context: Dyspnea is a common and distressing symptom in respiratory diseases. Despite advances in the treatment of various lung diseases, the treatment modalities for dyspnea remain limited. Objectives: This study aims to examine the effect of 20-minute mindful breathing on the rapid reduction of dyspnea at rest in patients with lung cancer, chronic obstructive pulmonary disease, and asthma. Methods: We conducted a parallel-group, nonblinded, randomized controlled trial of standard care plus 20-minute mindful breathing vs. standard care alone for patients with moderate to severe dyspnea due to lung disease, named previously, at the respiratory unit of University Malaya Medical Centre in Malaysia, from August 1, 2017, to March 31, 2018. Results: Sixty-three participants were randomly assigned to standard care plus a 20-minute mindful breathing session (n = 32) or standard care alone (n = 31), with no difference in their demographic and clinical characteristics. There was statistically significant reduction in dyspnea in the mindful breathing group compared with the control group at minute 5 (U = 233.5, n 1 = 32, n 2 = 31, mean rank 1 = 23.28, mean rank 2 = 37.72, z = −3.574, P < 0.001) and minute 20 (U = 232.0, n 1 = 32, n 2 = 31, mean rank 1 = 23.00, mean rank 2 = 36.77, z = −3.285, P = 0.001). Conclusion: Our results provide evidence that a single session of 20-minute mindful breathing is effective in reducing dyspnea rapidly for patients with lung cancer, chronic obstructive pulmonary disease, and asthma. © 2019 American Academy of Hospice and Palliative Medicine